Problems and perspectives of tourism development in the high Arctic. Case of Franz Josef Land - Shirokiy, Sergey (UiT The Arctic University of Norway, 2015)
Franz Josef Land, which is one of the most natural, pristine Arctic archipelagos is facing growing numbers of visitation and these numbers could continue to rise in the future. Despite its unique geographical position, nature and potential for tourism, it didn’t attract the attention of scientists investigating complex problems of tourism development in the high Arctic. This study aimed to identify the main problems of the development of tourism on Franz Josef Land and possible ways of solving them. Additionally, one of the aims of this study was to contribute to filling the gap in Arctic tourism research as there are limited numbers of studies that focus on tourism development on Franz Josef Land.